RL-based Routing Protocol to Minimize Channel Switching and User Interferences in Cognitive Radio Ad Hoc Network - SAFDAR, TAUQEER (2018)
In the existing network-layered architectural stack of Cognitive Radio Ad Hoc Network (CRAHN), channel selection is performed at the Media Access Control (MAC) layer. However, routing is done on the Network layer.